PRICE AND NON-PRICE COMPETITIVENESS FACTORS AND ECONOMIC DEVELOPMENT. A PVAR APPROACH - Cazacu, Ana-Maria Bancu (European Scientific Journal, ESJ, 2015)
The present study aims at identifying the link between economic growth and a wide variety of external competitiveness indicators, related to both price and non-price factors. Using data for European Union, we estimate a series of panel Vector Autoregression (PVAR) models and find that non-price indicators have a higher contribution in explaining GDP developments compared to traditional price and cost based measures of competitiveness. On the other hand, the results underline the broadness of competitiveness concept, as economic growth alone is found not to determine significant effects on the competitive capacity of economies.